New species and new records of Cryptarchinae (Coleoptera: Nitidulidae) from China - Xu, Qing; Zhang, Huan; Jelínek, Josef; He, Wen-Hui; Huang, Min (Zootaxa, 2026)
New species Glischrochilus (Librodor) parvorubellus sp. nov. from China and Nepal is described and illustrated. Two additional genus-group taxa, Glischrochilus s. str. and Eucalosphaera Jelínek, 1978, as well as eight species of the subfamily Cryptarchinae, i.e. Glischrochilus (Glischrochilus) cruciatus (Motschulsky, 1860), Cryptarcha strigata (Fabricius, 1787), C. dubia Grouvelle, 1890, Eucalosphaera feae (Grouvelle, 1892), E. grouvellei Kirejtshuk, 1987, E. oculipennis Kirejtshuk, 1994, E. ocularis (Reitter, 1875), and E. rufescens Kirejtshuk, 1987 are reported from China for the first time.